Karakteristik Biofilm Komposit CMC- Gliserol-Alginat dari Sargassum sp pada Perlakuan dengan Kalsium Klorida - Ali Ridlo; Sri Sedjati; Endang Supriyantini; Oetari Kusuma Putri (Universitas Diponegoro, 2022)
Bioplastics are plastics made from renewable raw materials such as polysaccharides, proteins and lipids. One of the alternative sources of bioplastic raw materials is hydrocolloid from seaweed, which is abundantly available in Indonesia, so that this hydrocolloid-based bioplastic is very prospective to be developed, and can increase the added value of seaweed. The physical and mechanical properties of alginate bioplastics can be improved by combining them with other materials into biocomposite materials that have superior properties and meet specifications. This study aims to determine the effect of calcium chloride (CaCl2) on the physical and mechanical properties of the CMC-Glycerol-Alginate composite bioplastic from Sargassum sp. Bioplastics were made by mixing 0.5 g of alginate flour, added CMC (1.5 g), and 100 ml of distilled water, then stirred with a magnetic stirrer for 10 minutes at 90oC. After that, the temperature was lowered to 40oC and 5 ml of glycerol was added and then homogenized again for 15 minutes. The mixture was filtered and then poured into a glass mold and the surface was leveled using a stainless steel cylinder, then dried in an oven at 80oC for 12 hours. After that the bioplastic is released from the glass plate. In the soaking method, the bioplastic sheets were immersed in a 2% CaCl¬2 solution for 5 minutes, then dried and stored in a desiccator. In the mixing method, 1 gram of CaCl¬2 was put directly into the alginate-CMC-glycerol mixture and homogenized with a magnetic stirrer at 90oC for 15 minutes, then printed on a glass plate, then dried at 100oC for 12 hours. CaCl2 treatment by mixing and soaking decreased elongation, tensile strength, biodegradability and transparency, but increased water resistance and thickness of the alginate-CMC-glycerol composite bioplastic, and changed the surface properties of the bioplastic to be rougher. No new functional groups were formed due to the interaction between alginate, CMC, glycerol, distilled water and CaCl2. Bioplastik adalah plastik yang dibuat dari bahan baku terbarukan seperti polisakarida, protein dan lipida. Salah satu alternatif sumber bahan baku bioplastik adalah hidrokoloid dari rumput laut yang tersedia melimpah di Indonesia, sehingga bioplastik berbahan hidrokoloid ini sangat prospektif untuk dikembangkan, serta dapat meningkatkan nilai tambah rumput laut.Sifat fisik dan mekanik bioplastik alginat dapat ditingkatkan dengan cara dikombinasi dengan bahan lain menjadi material biokomposit yang memiliki sifat unggul dan memenuhi spesifikasi.Penelitian ini bertujuan untuk mengetahui pengaruh kalsium klorida (CaCl2) terhadap sifat fisik dan mekanik bioplastik komposit CMC- Gliserol-Alginat dari Sargassum sp.Bioplastik dibuat mdengan mencampurkan tepung alginat sebanyak 0,5 g ditambahkan CMC ( 1,5 g), dan akuades 100 ml, lalu diaduk dengan magnetic stirrer selama 10 menit pada suhu 90oC. Setelah itu, suhu diturunkan sampai 40oC dan ditambahkan gliserol 5 ml lalu dihomogenkan lagi selama 15 menit. Campuran disaring lalu dituang dalam cetakan kaca dan diratakan permukaannya menggunakan silinder stainless steel, kemudian dikeringkan dalam oven pada suhu 80oC selama 12 jam. Setelah itu bioplastik dilepaskan dari pelat kaca. Pada metoda soaking lembaran bioplastik direndam dalam larutan CaCl2 2% selama 5 menit, lalu dikeringkan dan disimpan dalam desikator. Pada metoda mixing, CaCl2 sebanyak 1 gram dimasukkan langsung ke dalam campuran alginat-CMC-gliserol dan dihomogenkan dengan magnetic stirrer pada suhu 90oC selama 15 menit, lalu dicetak dalam pelat kaca, lalu dikeringkan pada suhu 100oC selama 12 jam. Perlakuan CaCl2 dengan cara mixing dan soaking menurunkan elongasi, kuat tarik, biodegradabilitas dan transparansi, tetapi meningkatkan ketahanan air dan ketebalan bioplastik komposit alginat-CMC-gliserol, serta mengubah sifat permukaan bioplastik menjadi lebih kasar. Tidak terdapat gugus fungsi baru yang terbentuk akibat interaksi antara alginat, CMC, gliserol, akuades dan CaCl2.